Knowledge and awareness of avulsed tooth management among dental surgery assistants at the Universiti Kebangsaan Malaysia (UKM) dental polyclinic - S. Nagarajan M. P. Sockalingam,; Ahmad Shuhud Irfani Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Tooth avulsion is a dental emergency that needs prompt treatment to minimise complications. This study aims to evaluate the knowledge and awareness of avulsed tooth management among dental surgery assistants at the UKM Dental Polyclinic. This survey research design of a 19- item questionnaire was distributed to 59 dental surgery assistants (DSAs). The questionnaire consisted of demographic profile questions and questions regarding awareness and knowledge of tooth avulsion and its immediate management. The results showed that 78% of DSAs at the Institute know about first aid management of avulsed teeth, with the majority being taught during their training course. Moreover, 96.2% of the DSAs know what tooth avulsion is and recognise it as a dental emergency. Although 75% of the DSAs have never previously handled any avulsed tooth case, 50% are confident in advising the public on what to do with an avulsed tooth at the time of injury. As for the specific management questions of an avulsed tooth, the responses from the DSAs varied according to the questions, ranging from 50% to 85%. DSAs at the Institute have varying levels of awareness and knowledge regarding tooth avulsion. Therefore, regular education programmes on dental trauma and its management will help improve the DSAs’ current knowledge and ability to manage avulsion injuries better in emergencies.